Acylation modification of konjac glucomannan and its adsorption of Fe (Ⅲ) ion. (November 2020) - Zhai, Haoying; Li, Dalin; Li, Minghan; Zou, Jinshan; Liu, Fuming; Chen, Fangyuan; Yan, Xingrong; Liu, Yiwu; Zhou, Wenjun
Abstract: A biodegradable adsorbent, modified konjac glucomannan (MKGM), was prepared by konjac glucomannan (KGM) acylated with phthalic anhydride catalyzed using concentrated sulfuric acid. The modified conditions such as reaction temperature, mass ratio of phthalic anhydride to KGM, catalyst dosage and reaction time were investigated, respectively. MKGM exhibited preferable adsorption performance for the removal of Fe (Ⅲ) ion. The adsorption behavior was discussed using the Langmuir and Freundlich isotherm models. The results showed that the Freundlich linear model was suitable for describing the adsorption process of Fe (Ⅲ). The maximum adsorption capacity of MKGM for Fe (Ⅲ) ion was 31.87 mg g −1 at 298 K. The kinetics studies suggested that adsorption process followed the pseudo-second-order model and the adsorption process was mainly controlled by both surface reactivity and intra-particle diffusion. Together with the evaluation of the thermodynamic parameters such as Gibbs free energy, enthalpy and entropy changes, the results indicated that the adsorption process of Fe (Ⅲ) was endothermic, feasible, and spontaneous in nature. Hence, as a bioadsorbent, the MKGM has a promising potential for the removal of Fe (Ⅲ) ion from aqueous solutions. Graphical abstract: Modified konjac glucomannan (MKGM), a biodegradable adsorbent for Fe (Ⅲ) ions, was synthesized through konjac glucomannan (KGM) acylated with phthalic anhydride catalyzed by concentrated sulfuric acid. Image 1 Highlights: MKGM was prepared by KGM acylated with phthalic anhydride catalyzed using concentrated sulfuric acid. Because of the coordination interaction between Fe (Ⅲ) and -COOH in MKGM, MKGM had good adsorption properties for Fe (Ⅲ). MKGM as a biodegradable adsorbent for Fe (Ⅲ) is of great significance to the treatment and recycle of iron-containing waste.